Peran Mahasiswa Dalam Meningkatkan Ekonomi Masyarakat Di Era Pandemi Covid-19 - Lestari, Nurni Arrina (PT. Alahyan Publisher Sukabumi, 2023)
The Thematic KKN activity carried out by Muhammadiyah Students in Sukabumi City is an experiential activity for learning, applying, and developing science and technology outside the campus environment involving the local government, the community, and the private sector. This Thematic KKN aims to solve problems faced by the local community, it is hoped that students can help overcome these problems and achieve targets related to existing problems. To help overcome problems and achieve targets, students create several work programs related to food security, preparation of financial reports, and digital marketing. Like food security, the community was given insight into the use of home yards for growing red spinach, taught, and water spinach hydroponics. The use of home yard land can pay off, that is, reduce the cost of buying vegetables. The preparation of financial reports for MSME actors is done so that MSME actors can easily apply for KUR loans. Meanwhile, digital marketing is the use of social media as a place to market products from MSMEs.